LABOR SATISFACTION AND PERFORMANCE OF PEOPLE IN THE COMPANY PROTEGE ORIENTE S.A., PUCALLPA, 2018 - Bollet Ramírez, Frank (2019)
The present investigation is an undergraduaThis research is an undergraduate thesis that aimed to determine the relationship between job satisfaction and job performance in the staff of the company Protege Oriente S.A. In the study two instruments were used, in the first questionnaire of the variable I: job satisfaction, was adopted from the "Scale of Labor Satisfaction (SL-SPC)", of S. Palma, 2005, which originated a general diagnosis of the attitude toward work, detecting how pleasant or unpleasant the person considered his work. The second questionnaire of the variable II, the performance of the people, adapted from the work of Quispe E. 2015. The design that was used was the correlation. Applying the statistics, it was determined that there is a significant relationship between job satisfaction and the performance of people in the company Protege Oriente SA, with the "r" of Pearson of 0.456, considered as a weak positive correlation, and that the level of significance had a value: s = 0.000 ˂ 0.05, the coefficient was significant at the level of 0.000 (100% confidence that the correlation is true and 0.0% probability of error). KEYWORDS: Labor Conditions, Task Meaning, Personal Recognition.